Antecedents of Supply Chain Performance: A Case of Food Retail Industry - Chriss Narick Mangoukou Ngouapegne; Elizabeth Chinomona (Journal of Economics and Behavioral Studies, 2018)
Food retail industry plays an important part in gross domestic product (GDP). Buyers and suppliers in this industry work in collaboration with each other to achieve an optimal supply chain performance. The purpose of this study is to investigate the drivers of supply chain performance in the food retail industry in Gauteng province. These drivers are known as buyer- supplier trust (BST), buyer- supplier commitment (BSC) and supply chain relationship longevity (RL). This study adopted a quantitative method where a questionnaire was used to collect data from 429 food retailers in the Gauteng province. The study used a convenience sampling technique to select respondents. The Statistical Package for the Social Sciences (SPSS) 24.0 and Smart PLS were used to assist in the data analysis. The results of the research revealed that buyersupplier trust, buyer- supplier commitment and RL have a strong, positive and important impact on supply chain performance. Based on the results of this study, it can be concluded that to achieve supply chain performance, business’s operators should develop a significant relationship based on trust, commitment and relationship longevity. Furthermore, the results of this study provide useful insights on how businesses should benefit from trust, commitment and relationship longevity as well as how to improve supply chain performance. Practical and theoretical contributions, implications and recommendations are provided.